Search for colour reconnection effects in e+e− → W+W− → hadrons through particle-flow studies at LEP - Dova, María Teresa (2003)
A search for colour reconnection effects in hadronic decays of W pairs is performed with the L3 detector at centre-of-mass energies between 189 and 209 GeV. The analysis is based on the study of the particle flow between jets associated to the same W boson and between two different W bosons in qqq ̄ q events. The ratio of particle yields in the different interjet regions is found to be sensitive to colour reconnection effects implemented in some hadronization models. The data are compared to different models with and without such effects. An extreme scenario of colour reconnection is ruled out.